Trichoderma virens ISOLATED FROM COCOA PLANTATION IN ACEH AS BIODECOMPOSER COCOA POD HUSK - Rina Sriwati; Tjut Chamzurni; Bukhari Bukhari; Anwar Sanjani (Universitas Syiah Kuala, 2013)
Sustainable development on cocoa farming have been places great emphasis on the management of natural resources for Cocoa pod husk. Until now, there has been much public attention for a farming waste, environment polluting and a place to develop various diseases, especially fungal Phytopthora. To overcome these problems, it needs to utilize alternative cocoa pods. The aims of this study were: (1) to determine the potential use of Trichoderma virens isolated from cocoa plantation in Aceh as bio-decomposer in the composting process cocoa pods. The composition of potential use experiment; Manure+Trichoderma (PT); Cocoa pod husk+Trichoderma (KT); Cocoa pod husk + Manure (KP); Cocoa pod husk +Manure+Trichoderma (KPT) has been tested. The analysis result showed that the combined use of Trichoderma virens compost although no effect on the color, texture and smell of compost but could be effect on characterized of compost maturity by characteristics of C/N compost. The content of C/N compost on all treatments in accordance with the standard compost maturity thus considered quite feasible to be applied to the crop.